The Influence of Javanese Language Usage in The Sociodrama Method of Increasing Politeness Behavior of Children Ages 5-6 Years - Yuliyani, Efa Rini; Mukminin, Amirul (BELIA: Early Childhood Education Papers, 2020)
Politeness is the norm that regulates how to behave and behave in daily life so that people can be valued and liked. Playing socio-drama can be one of the activities that are fun for children and can be used as a means to develop children's polite behavior using Javanese Krama at the same time. Javanese Krama Language is a language with a vocabulary that is used to communicate with parents as a sign of polite and reluctance to the older person. The formulation of the problem in this study is whether there is an increase in the children's politeness with the use of Javanese Krama in the socio-drama method. The purpose of this study is to explain the improvement in the children's politeness with the use of Krama Javanese in the socio-drama method. This research is a quantitative approach with an experimental method by one group pretest-posttest design. The sample in this study is kindergarten student BA Aisyiyah Kandangwangi. The data collection method uses a Likert scale. The sampling technique used is a non-probability sampling technique with a type of purposive sampling. The result of this study indicates that the conducted hypothesis test through a significant 2-tailed test is 0.00. The hypothesis is accepted if the significance value < Î±, with Î± = 0.05. In the calculation of this study obtained a significance value < Î±, that is 0.00 <0.05 so Ha is accepted. So, it can be concluded that there is an improvement in the children's politeness with the use of Javanese Krama in the application of socio-drama method.